Compact accelerator based neutron sources (IAEA-TECDOC ;, 2021)
"The production of neutrons by accelerators began in the 1970s with construction of powerful proton accelerators to access neutrons via spallation. At the same time, low energy driven neutron processes emerged for neutron production using electron accelerators, ion beam accelerators, cyclotrons, and low energy linear accelerators. This wide variety of accelerator based neutron sources have come to be referred to as 'compact accelerator based neutron sources' (CANS). This publication provides an overview of the various types of CANS technologies that are currently available or planned in the near future. It illustrates many of the analytical and other applications of neutrons. Given the wide variety of power and costs, the publication also aims to show that in addition to replacing national medium flux research reactors for certain functions, smaller regional neutron sources may become viable, which may eventually broaden access to neutron facilities." -- Publisher's website.